Enhancement of Water Quality for Shatt Al-Arab River and NW Arabian Gulf BY Granular Activated Carbon and local Sand - Amteghy, Ali H. (University of Thi-Qar Journal of Science, 2014)
Shatt Al-Arab river is considered as one of the most important industrial, irrigation and drinking water resources. the river at its end discharges to Arabian Gulf. Water samples were collected from seven sites along the Shatt Al-Arab river and North West Arabian Gulf during summer, winter and spring 2010 and were determined some physico-chemical properties and heavy metals contaminations. The physical and chemical parameters of water were included the Temperature (T), Hydrogen activity (pH), Electric Conductivity (EC),Total Hardiness(TH),Calcium (Ca) , Magnesium (Mg), Sodium (Na) , Potassium (K), Chloride (Cl), Sulfate (SO4), Nitrate (NO3), Phosphate (PO4), Silicate (SiO4), Manganese (Mn), Iron (Fe), Copper (Cu), Nickel (Ni), Cobalt (Co) and Lead (Pb). The results of the study showed a differences between the studied properties and a clear significant differences were noticed during the seasons of the year and sites. The pH of the studied area varies from neutral to weak basic, and showed high conductivity (Total salinity) in addition to increase the concentration of TH, Ca, Mg, Na, K, Cl, SO4, and NO3 in the water river according to the drinking water criteria of (WHO), and Iraqi Standard limits (SI). Of the within . The mean of TH was above the international limits therefore it’s classified as hard water. To decrease the high level of the chemical parameters :the water Shatt Al-Arab ,four different filtration systems were used . present study it was compared between activated carbon, activated carbon-sand filters.